Experimental study on behavior of sifcon beam-column joints subjected to cyclic loading - Balaji, S.; Thirugnanam, G.S. (Journal of Structural Engineering, 2024)
Beam-column joint is an important component of a reinforced concrete moment resisting frame and should be designed and detailed properly, especially when the frame is subjected to earthquake seismic forces. Failure of beam-column joints is governed by bond and shear failure mechanism which are brittle in nature. Therefore, all international codes recommend to provide adequate anchorage to longitudinal bars and confinement of core concrete in resisting shear. In the present study, investigations are carried out to study the behavior of exterior SIFCON beam-column joints under cyclic loading. The specimens are detailed as per IS 13920 – 1993 recommendation. A total number of six specimens corresponding to two test series are cast and tested under cyclic loading to study the load deformation behavior, ductility associated parameters, ultimate load carrying capacity and failure characteristics. The concrete mix for RC beam-column joints has been designed to obtain a concrete grade of M30. For SIFCON beam-column joints fibre volume fraction was 9%. The steel fibres used in the study were round crimpled fibres having 0.5 mm diameter and aspect ratio of 60. Results indicate that the SIFCON beam-column joints have improved cracking behavior in terms of significant increase in first crack load and the formation of larger number of finer cracks. The ultimate load carrying capacity, stiffness, ductility and energy absorption are increased a greater extent for SIFCON beam-column joints compared with that of conventional RC beam-column joints.